Cytogenetic and molecular data demonstrate that the bryconinae (ostariophysi, bryconidae) species from southeastern Brazil form a phylogenetic and phylogeographic unit - Travenzoli, Natália Martins; Silva, Priscilla Caroline; Santos, Udson; Zanuncio, José Cola; Oliveira, Claudio [UNESP]; Dergam, Jorge Abdala (Public Library Science, 2015)
Brycon spp. occur in Neotropical watersheds to the west and east of the Andes, and as they are sensitive to anthropogenic changes, many these species are endangered in southeastern Brazil. Coastal rivers in southeastern Brazil are characterized by the presence of relatively few freshwater fish species and high endemism of this fauna. The objective of this study was to examine whether Brycon spp. occurring in the coastal basins of southeastern Brazil are monophyletic, using cytogenetic data, mitochondrial, and nuclear molecular markers. All the species showed a diploid number of 50 chromosomes, a conserved number within the subfamily Bryconinae. However, the karyotypic formulas were unique to most species, including Brycon devillei (26m+22sm+2st), Brycon ferox (26m+12sm+12st), Brycon insignis (22m+20sm+8st), Brycon opalinus, and Brycon vermelha (24m+20sm+6st), indicating the prevalence of pericentric and paracentric inversions in the chromosomal evolution of these species. All of them had nucleolar organizer regions in the first pair of subtelocentric chromosomes and no equilocal distribution of heterochromatin in the first pair of chromosomes of the karyotype. These two features, not seen in any other Brycon spp. examined to date, indicate that Bryconinae species from the Brazilian southeastern coastal basins, including the monotypic genus Henochilus, are monophyletic. Also, this is the first study that reports NOR location and C-banding patterns as synapomorphies for a Neotropical fish species group. The monophyly was also supported by a phylogenetic analysis of 16S rDNA (16S), cytochrome oxidase subunit I (COI), alpha-myosin (MYH6) genes and S72 intron molecular data. Our results partially corroborate the Brycon acuminatus group proposed by Howes in 1982: our proposed clade keeps B. devillei, B. ferox, and B. insignis; but it also includes B. opalinus, B. vermelha, and H. weatlandii whereas it excludes B. nattereri. The phylogeographic unit formed by Bryconinae species in southeastern Brazil reflects the long and isolated paleohydrological history of these coastal basins relative to the continental watersheds.